2013
DOI: 10.1111/avj.12025
|View full text |Cite
|
Sign up to set email alerts
|

Failure of transfer of passive immunity and agammaglobulinaemia in calves in south‐west Victorian dairy herds: prevalence and risk factors

Abstract: There is considerable potential to improve the transfer of passive immunity in dairy herds in south-west Victoria. The prevalence of both FTPI and agammaglobulinaemia is likely to be reduced by collecting calves from the calving area twice daily and hand-feeding them extra colostrum immediately after their removal from the calving area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
72
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 24 publications
9
72
1
2
Order By: Relevance
“…The overall and mean (range) within-herd prevalences of FTPI were 41.9 and 36.2% (0.0-83.3%), respectively. Vogels et al (2013) estimated FTPI among 100 herds in southwest Victoria measuring serum total protein, also finding a high prevalence: 38% of calves experienced FTPI and more than two-thirds of the herds had more than 25% of calves with FTPI. Our survey found that 23.6% of respondents let calves suck colostrum from their dams and 71.6% separated calves from their dams >6 h after calving.…”
Section: Ftpi Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…The overall and mean (range) within-herd prevalences of FTPI were 41.9 and 36.2% (0.0-83.3%), respectively. Vogels et al (2013) estimated FTPI among 100 herds in southwest Victoria measuring serum total protein, also finding a high prevalence: 38% of calves experienced FTPI and more than two-thirds of the herds had more than 25% of calves with FTPI. Our survey found that 23.6% of respondents let calves suck colostrum from their dams and 71.6% separated calves from their dams >6 h after calving.…”
Section: Ftpi Prevalencementioning
confidence: 99%
“…Some studies have investigated colostrum quality parameters (Phipps et al, 2016;Chuck et al, 2017), 8353 the prevalence of failure of transfer of passive immunity (FTPI; Vogels et al, 2013), the prevalence of common enteropathogens causing neonatal calf diarrhea (NCD; Izzo et al, 2011b), and calf-rearing practices (Phipps et al, 2018) on Australian dairy farms. However, these studies were limited to a particular region and, to the authors' knowledge, no study has investigated these parameters together.…”
Section: Introductionmentioning
confidence: 99%
“…Calves that fail to ingest or absorb sufficient colostral IgG, resulting in a serum IgG concentration <1,000 mg/ dL, suffer from failure of transfer of passive immunity (FTPI; Vogels et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3 It is also common practice to supplement the dairy calf with additional colostrum once the calf has been removed from the dam. 3 It is also common practice to supplement the dairy calf with additional colostrum once the calf has been removed from the dam.…”
mentioning
confidence: 99%
“…3 It is also common practice to supplement the dairy calf with additional colostrum once the calf has been removed from the dam. 3 The process of obtaining colostrum for supplementing calves requires harvesting colostrum from the first milking post calving, storing the colostrum and then feeding it to the dairy calves. 3 Calves that were not supplemented with additional colostrum were 3-fold as likely to have failure of passive transfer (FPT).…”
mentioning
confidence: 99%